Licensing and Promotion of Investments through the Bintan Regency Area Enterprise Agency - Adhayanto, Oksep; Yolanda, Glory; Suwardi, Nurhasanah; Kurnianingsih, Fitri; Indra, Mexsasai (Acta Universitatis Danubius. Juridica, 2022)
The goal of this research was to look at the licensing and promotion activities of the Bintan Regency Regional Concession Agency in terms of promoting investment as a source of regional revenue for Bintan Regency. This is a qualitative descriptive study using an empirical methodology. The study will take place at the Bintan Regency's One-Stop Integrated Service Investment Office and the Bintan Area Concession Agency. Data collection techniques include interviews and a review of the literature. The research concluded that the Bintan Regency Regional Concession Agency performed well in terms of licensing and investment promotion in the Bintan Regency. This is shown by the rising number of investments made.